2020
DOI: 10.3390/pathogens9010053
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-cas3 of Salmonella Upregulates Bacterial Biofilm Formation and Virulence to Host Cells by Targeting Quorum-Sensing Systems

Abstract: Salmonella is recognized as one of the most common microbial pathogens worldwide. The bacterium contains the clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated (Cas) systems, providing adaptive immunity against invading foreign nucleic acids. Previous studies suggested that certain bacteria employ the Cas proteins of CRISPR-Cas systems to target their own genes, which also alters the virulence during invasion of mammals. However, whether CRISPR-Cas systems in Salmonella have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 93 publications
2
61
1
Order By: Relevance
“…A recent study on the effects of deleting cas 3 in Salmonella enterica showed no differences in liquid growth. In contrast to our results, those researchers found a decrease in intracellular survival in the mutant ( 53 ). The expression profiles of wild-type P. gingivalis and the cas 3 mutant were very similar when the bacteria were placed in human serum-based medium, but when they colonized the human macrophage-like THP-1 cell line, the transcriptome profiles of the wild-type and mutant strains were very different.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A recent study on the effects of deleting cas 3 in Salmonella enterica showed no differences in liquid growth. In contrast to our results, those researchers found a decrease in intracellular survival in the mutant ( 53 ). The expression profiles of wild-type P. gingivalis and the cas 3 mutant were very similar when the bacteria were placed in human serum-based medium, but when they colonized the human macrophage-like THP-1 cell line, the transcriptome profiles of the wild-type and mutant strains were very different.…”
Section: Discussioncontrasting
confidence: 99%
“…The only activities that were altered under both sets of growing conditions were activities associated with adhesion, probably because fimbrial genes, including fim A, were downregulated in the mutant. In S. enterica , deletion of cas 3 leads to downregulation of saf A, saf B, saf C, and saf D genes in the fimbrial operon ( 53 ). The mechanisms by which cas 3 controls levels of transcription of fimbrial genes remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that strains carrying CRISPR systems were enriched for biofilm-associated genes (>70 vs. <2% non-CRISPR strains), suggesting a link between CRISPR immunity and biofilm formation (Mangas et al, 2019). Previous research has shown that Cas3 endonuclease is involved in the control of biofilm formation in both gram-positive and gram-negative bacteria (Tang et al, 2019;Cui et al, 2020).…”
Section: Recent Developmentsmentioning
confidence: 99%
“…In addition to adaptive immunity, noncanonical functions have been suggested for the components of CRISPR-Cas systems (Cas proteins, crRNAs and other CRISPR-associated RNAs) that are implicated in the control of bacterial pathogenesis and physiology [ 163 , 164 , 165 , 166 , 167 ]. The molecular mechanisms of CRISPR-Cas-mediated control of gene expression remain in many cases to be explored, but important links of these regulatory processes with virulence, biofilm formation and envelope stress response could be emphasized in several pathogens, i.e., Francisella novicida , Neisseria meningitidis, Campylobacter jejuni, Legionella pneumophila , L. monocytogenes, and P. aeruginosa [ 164 , 166 , 168 ]. Interestingly, a recent work suggests targeting of quorum-sensing systems by CRISPR-Cas in Salmonella to mediate virulence and biofilm formation regulation [ 168 ].…”
Section: Srnas Regulating Host-pathogen Interactionsmentioning
confidence: 99%